Efektivitas E-LKPD IPA Model Socioscientific Inquiry Based Learning (SSIBL) untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik - I Made Tri Pramana Putra; A. A. Istri Agung Rai Sudiatmika; I Nyoman Suardana (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of this study was to test the effectiveness of E-LKPD IPA through Socientific inquiry-based learning (SSIBL) Model in improving students’ scientific literacy skills. The research type used is pre-experimental with one group pretest-posttest design. The effectiveness test was undertaken at SMP Negeri 3 Kubutambahan in the even semester of the 2022/2023 school year. The research subjects were students of class VII A, it consisted of 36 students. The research instrument used was a scientific literacy test which adjusted for scientific literacy indicators in PISA 2018. The data analysis used was descriptive analysis in the form of an average score (mean) and a normalized n-gain score obtained from the pretest and posttest results. The results indicated that a normalized n-gain was 0.59 in the medium category and the results of the one-sample proportion test showed that students’ mastery of scientific literacy was more than or equal to 75%. Thus, E-LKPD of SSIBL model is effective in improving student’s scientific literacy skills